TESTING THE EFFECTIVENESS OF BIDARA LEAF ETHANOL EXTRACT (Ziziphus mauritiana L.) IN GEL PREPARATIONS FOR BURN WOUNDS IN MALE RABBIT (Oryctolapus cuniculus) - Sulasmi, Sulasmi; Sanjaya, Angga Nugraha; Bangun, Sofia Elia Sari; Cahaya, Cucu Arum Dwi (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2022)
Abstract Bidara plants have many benefits in the treatment of sore skin, ulcers, and burns. Burns are a form of tissue damage or loss caused by contact with a heat source such as fire, hot water, electricity, radiation, or corrosive substances. This study aims to determine the effectiveness of the ethanol extract of bidara leaf in healing burns in male rabbits compared to bioplacenta. This study used an experimental method of maceration extraction using 96% ethanol. To test the effect of burns, 15 test animals were grouped into five groups, each of which used three test animals. The treatment group was a gel-based negative control group, a positive bioplacenta control group, and a treatment group with bidara leaf ethanol extract at concentrations of 5%, 10%, and 15%. The results of the research on the effectiveness of healing burns in the three formulations, namely a concentration of 15%, showed faster healing of wound diameter in male rabbits compared to concentrations of 5% and 10% but were not more effective when compared to bioplacenta ointment. Keywords: Bidara leaf ethanol extract, burns, ointment and bioplacenton